Processo penal “fast-food”: concentração de atos processuais em audiências de custódia após a Lei 13.964/2019 - MACEDO, Mariana Neiva da Luz (2022)
It is analyzed the possibility of concentrating procedural acts, especially of instruction, when the custody hearing is realized, in order to verify the impact of Law 13,964 / 2019. Therefore, it is realized a bibliographical and documentary research, which uses the deductive method to make considerations about how the doctrine, law and jurisprudence behave deal with the problem. At the first moment, it was necessary to present the institute's presentation concept, purposes and historic. Then, it was verified how the criminal prosecution is willing in the national legal system and the importance of the procedural form. In the end, situations were identified in which procedural acts are being concentrated in custody hearings headquarter and which are their implications. It appears that the custody hearing is essential for the humanization of the criminal process, it allows the judiciary to have a real view of the functioning of the criminal justice system and reduces the unnecessary entry of individuals into the prison system. Criminal jury instructions and custody hearings have predetermined forms, guaranteeing equality of arms between procedural actors, which are assured by the constitutional text and that the concentration of procedural acts in custody hearings is incompatible with the criminal justice system adopted by Brazil and with the inherent purposes to the custody hearing institute. It is observed that Law 13,964 / 2019 is silent about the subject, however, it requires an interpretation that must follow the constitutional commandments, so this practice must be restrained, in order not to cause harm to the defendant / accused, and so the purposes intended for the execution of the custody hearing.